Effect of wave-induced Stokes drift on the dynamics of ocean mixed layer - 王智峰 吴克俭 董胜 邓增安 张晓爽 (Chinese journal of oceanology and limnology, 2015)
The wave-forcing ‘Coriolis-Stokes forcing’ and ‘Stokes-vortex force’ induced by Stokes drift affect the upper ocean jointly. To study the effect of the wave-induced Stokes drift on the dynamics of the ocean mixed layer, a new three-dimensional (3D) numerical model is derived using the primitive basic equations and Eulerian wave averaging. The Princeton Ocean Model (POM), a 3D primitive equation ocean model is used with the upper wave-averaged basic equations. The global ocean circulation is simulated using the POM model, and the Stokes drift is evaluated based on the wave data generated by WAVEWATCH III. We compared simulations with and without the Stokes drift. The results show that the magnitude of the Stokes drift is comparable with the Eulerian mean current. Including the Stokes drift in the ocean model affects both the Eulerian current and the Lagranian drift and causes the vertical mixing coefficients to increase.